The enigma of the weekend effect - Mathew, Anoop; Fyyaz, Saad Ahmed; Carter, Paul Richard; Potluri, Rahul (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Increased mortality associated with weekend patient admissions is a global and pervasive phenomenon. Particularly in the UK, this has recently been the subject of intense media, political and scientific scrutiny (1,2). The “weekend effect” has often been highlighted with farfetched conclusions regarding the likely causes. Specifically, it has been implied that the weekend effect is a result of the failure of healthcare management organizations to improve processes of care, including ensuring 24/7 accessibility to life-saving diagnostic and therapeutic procedures (2-4). As such, the body of evidence that has emerged over the last few years on the weekend effect has resulted in the UK government implementing a series of changes to facilitate the adoption of 24/7 hospital care across the National Health Services (1,4), engendering much controversy.